2016
DOI: 10.3136/fstr.22.59
|View full text |Cite
|
Sign up to set email alerts
|

Rind Color Development in Satsuma Mandarin Fruits Treated by Low-intensity Red Light-emitting Diode (LED) Irradiation

Abstract: Here, we investigated the effect of irradiation by a low-intensity red light-emitting diode (LED) (photon flux μmol•m_ 2 •s _ 1 ) on rind color development in Satsuma mandarins after harvesting at two different periods. In the early harvest fruit, the a* value for Satsuma mandarin peel treated by red LED irradiation was 2.7 and 2.4 times higher than that for the dark treatment fruit at 4 and 8 days irradiation, respectively. In the commercial harvest fruit, the a* value of the peel treated by red LED irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…syringae strain B728a [9]. In addition, red light is an effective postharvest treatment, which has also been applied in the preservation of many kinds of fruits, such as accelerating the ripening of green tomato fruit [10], extending the storage period for broccoli [11], promoting the color transformation of fruit peel of harvest mandarins [12], and increasing anthocyanin accumulation in grape berry [13]. However, the effects of red light irradiation on pitaya fruit is not clear after harvest.…”
Section: Introductionmentioning
confidence: 99%
“…syringae strain B728a [9]. In addition, red light is an effective postharvest treatment, which has also been applied in the preservation of many kinds of fruits, such as accelerating the ripening of green tomato fruit [10], extending the storage period for broccoli [11], promoting the color transformation of fruit peel of harvest mandarins [12], and increasing anthocyanin accumulation in grape berry [13]. However, the effects of red light irradiation on pitaya fruit is not clear after harvest.…”
Section: Introductionmentioning
confidence: 99%
“…Light is important to the development of the photosynthetic apparatus and is involved in both degreening and regreening in the peel of citrus fruit. Yamaga et al (2016) reported that low-red LEDs increased the a* value of peel in early-harvest satsuma mandarin fruit. In red grapefruit, high intensity light inhibited chlorophyll breakdown and carotenoid accumulation in the peel of fruit located on the branch (Lado et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In satsuma mandarins, Izumi et al (1992) reported that high-intensity sunlight promoted the coloration of fruit. Yamaga et al (2016) indicated that exposure to low-intensity red light-emitting diode (LED) irradiation led to development of a degree of This article is an Advance Online Publication of the authors' corrected proof. Note that minor changes may be made before final version publication.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that red LED influences the quality of citrus flavedo. Yamaga et al (2016) reported that the a* value (red color) of the peel of satsuma mandarins exposed to red LED irradiation was 1.2 and 1.4 times higher than that of fruit subjected to dark treatment with 4-8 days of irradiation, respectively. Although red LED irradiation influenced the color of rind to a certain degree, it did not influence internal fruit quality.…”
Section: Plant Responses To the Wavelength And Intensity Of Lightmentioning
confidence: 99%